The effects of climate change on employee health and safety: Evidence of existing studies - Bangura, Samuel (Edelweiss Applied Science and Technology, 2024)
An escalation in carbon dioxide emissions has increased greenhouse gases, directly influenced climate change and subsequently impacted the health and safety of employees. The objective of this review is to analyse the effects of climate change on employee H&S and propose strategies to alleviate these impacts. In line with the preceding assertion, an integrative literature review was conducted across multiple online research databases to consolidate findings from various studies. Databases utilised included Web of Science, Emerald, Science Direct, Google Scholar, Scopus, SpringerLink, and ResearchGate. Key information gathered includes publication year, title, study purpose, sample size, and findings. The conclusions drawn were based on a comprehensive review of available evidence. The study found that climate change poses significant risks to the H&S of employees, particularly about climate-related illnesses. The research has also indicated that preventative actions can be implemented to minimise these impacts. This study underscores the significance of addressing climate change to safeguard the welfare of employees.